Programa educativo de investigación para mejorar las competencias investigativas de los estudiantes de Maestría en Educación de la Universidad Nacional de la Amazonía Peruana Iquitos 2023 - Tejedo Lozano, Marco Antonio (2025)
This evaluative study, based on a pre-experimental one-group design, aimed to analyze the impact of a social skills program on strengthening various competencies among master's degree students. The research employed a quantitative approach with descriptive and inferential analysis to assess instrumental, reflective, and social competencies before and after the intervention. Descriptive results revealed improvements in performance levels across all assessed competencies. Notably, high-level performance increased in areas such as English language proficiency (from 3% to 20%), scientific documentation techniques (from 7% to 30%), data analysis software use (from 0% to 12%), and problem planning (from 3% to 20%). However, persistent weaknesses were identified in practical application, collaborative work, and methodological development, highlighting the need to strengthen research training in these areas. Inferentially, the Shapiro-Wilk test confirmed data normality, allowing the application of the paired samples t-test. The results demonstrated statistically significant differences (p < 0.05) in overall pedagogical management and across its dimensions: planning and organization, classroom management, teaching and learning, and assessment with feedback. Therefore, the social skills program had a positive and significant effect on the professional and research development of graduate students. These findings support the effectiveness of training programs aimed at enhancing research and pedagogical competencies at the graduate level, while also revealing areas in need of further development to establish a strong, collaborative, and applied research culture.